SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMK PGRI 2 KARAWANG - Abdussomad, Abdussomad; Akmaludin, Akmaludin; Adiwiharja, Cep (STMIK ANTAR BANGSA, 2016)
Abstract— SMK PGRI 2 Karawang is a form of embodiment in educating the young generation of Indonesia. With the development of a growing number of students from year to year, required precision and accuracy in providing precise and accurate information for students without the repetition of the same data. SMK PGRI 2 Karawang so requires an information system that supports the presentation of the school's academic information. To the authors tried to handle the problem by designing a Web-Based Information System Academic In SMK PGRI 2 Karawang. Academic information system is one solution to provide an information quickly and accurately. web-based academic information system is very useful in providing convenience to both the teacher or the student. Web-Based Academic Information System is the perfect solution to create an information system that is effective and efficient. Intisari— SMK PGRI 2 Karawang merupakan sebuah bentuk perwujudan dalam mendidik genarasi muda bangsa Indonesia. Dengan perkembangan jumlah siswa yang terus bertambah dari tahun ke tahun, dituntut ketepatan dan ketelitian dalam memberikan informasi yang tepat dan akurat kepada siswa tanpa adanya pengulangan data yang sama. SMK PGRI 2 Karawang sangat membutuhkan adanya sebuah sistem informasi yang menunjang dalam proses penyajian informasi akademik sekolah. Untuk itu penulis mencoba menangani masalah tersebut dengan merancang suatu Sistem Informasi Akademik Berbasis Web Pada SMK PGRI 2 Karawang. Sistem informasi akademik merupakan salah satu solusi untuk memberikan sebuah informasi secara cepat, tepat dan akurat. sistem informasi akademik berbasis web sangat berguna dalam memberikan kemudahan baik kepada pengajar ataupun pelajar. Sistem Informasi Akademik Berbasis Web merupakan solusi yang tepat untuk mewujudkan sebuah sistem informasi yang efektif dan efisien. Kata Kunci— Sistem, Informasi, Akademik, Website